Fabrication of Self-Cleaning Perfluoroacrylate Blend Films by Spray Coating Method - Sema Nur Belen; Özge Ünzal; Uğur Cengiz (Journal of Advanced Research in Natural and Applied Sciences)
The superhydrophobic surfaces are contained two essential principles. First, low surface energy polymers, such as fluoropolymers pushing the liquid onto the surface are necessary. The surface roughness is the second necessity to obtain superhydrophobicity, providing air packets between the roughness and reducing surface interaction with the liquid. This study fabricated the superhydrophobic blend coating using a spray coating method. The flat surface of PFMA homopolymer synthesized in scCO2 medium was fabricated free meniscus coating method due to the lack of solubility in the conventional solvent. To overcome the solubility problems of the PFMA, the p(Perfluoromethacrylate-ran-Styrene) copolymer was fabricated in a scCO2 medium. Blend solutions are prepared to reduce costs and provide high hydrophobicity by using p(Perfluoromethacrylate-ran-Styrene) copolymer and PS homopolymers. The surface roughness of the blend films was altered using silica nanoparticles coated on a glass slide by a spray coating. The surface morphology was characterized by SEM analyses indicating that double-scale surface morphology was obtained by increasing the SNp of the composite solution. The water contact angle indicated that the superhydrophobic rough surface was obtained with TMS70 and PS blend formation having 33.0 % PS and 12.5% silica nanoparticles.